Postnatal counseling promotes early initiation and exclusive breastfeeding: a randomized controlled trial - Beyene, Belda Negesa; Wako, Wako Golicha; Moti, Dureti; Edin, Alo; Debela, Derese Eshetu (Frontiers in Nutrition, 2025)
BackgroundBreastfeeding plays a crucial role in promoting the health and wellbeing of both mothers and their infants, contributing to healthier populations and reducing long-term healthcare costs. Encouraging breastfeeding through education, support, and policies is essential for maximizing these benefits. The purpose of this study was to evaluate the impact of immediate postpartum counseling on early initiation of breastfeeding rates and exclusive breastfeeding in Bule Hora Teaching and Yabelo General Hospitals.MethodsA cluster randomized single-blinded trial was conducted on 224 postpartum women (112 in the intervention group and 112 in the control group) from January 1, 2023, to May 30, 2023. The effects of immediate postpartum counseling and its associated variables on early initiation and exclusive breastfeeding practices were evaluated using logistic regressions. A p-value of less than 0.05, a 95% confidence interval, and an adjusted odds ratio were used to determine statistical significance.ResultsThe proportion of early initiation of breastfeeding was significantly greater in the intervention group than in the control group (54.1% vs. 45.9%, p = 0.001), and exclusive breastfeeding practice were also significantly greater among women who received immediate breastfeeding counseling than among those who did not receive it (61.9% vs. 38.1%, p = 0.015). Those mothers who had an ANC visit for their pregnancy were three times more likely (AOR = 3.01, 95% CI = 1.12–8.1) to initiate breastfeeding. Having good knowledge regarding breastfeeding made them six times more likely to initiate breast-feeding earlier (AOR = 6.18, 95% CI = 1.77–21.57). Women who received counseling (AOR = 3.36, 95% CI: 1.83–6.16) and women who had good knowledge about breastfeeding (AOR = 1.88, 95% CI: 1.01–3.49) were significantly associated with exclusive breastfeeding practices.ConclusionThis study revealed that immediate postpartum breastfeeding counseling can positively influence both early initiations of breastfeeding and exclusive breastfeeding practices. Providing sustained education to women regarding early initiation and exclusive breastfeeding practices should be strengthened.